STUDY OF CONTROL INHOMOGENEITIES OF THE DIELECTRIC BETWEEN METAL PLANES OF MICROWAVE DEVICES IN PHASED ARRAY ANTENNAS - Antonenko, Anton; Geraimchuk, Michael (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
This article describes the phase shifters, based on micro-electromechanical elements connected to phased array antennas which operating in the frequency range 2–30 GHz. Estimations of controllability characteristics located between the metal dielectric planes, heterogeneity as an element of a micromechanical controlled microwave-devices. It is shown that when microdisplacements metal plane above the dielectric effective permittivity inhomogeneities it may vary from the values of the relative permittivity of the dielectric to one unit. Criteria required is small dielectric thickness or frequency at which the dielectric effect is not observed. The results can be used in the design of electromechanical devices managed using the MPN of piezoelectric and electrostrictive actuators or MEMS.